The involvement level of extension agent in activities based on rice check technology at IADA Pekan Pahang, Malaysia - Yusuf, Munifah Siti Amira; Hassan, Salim; Oluwatoyin, Olagunju; Mohd Hanif, Nor Latifah (International Organization of Scientific Research, 2017)
Rice is a staple food for Malaysian and productivity must be focus upon in order to meet the increasing demand as the country growing population increases. Government had to produce a new and good variety of paddy which is MR219 and also to provide the Technology of Rice check as a manual and guideline to the extension agents to meet the needs of the farmers. However, the current yield at IADA Pekan is only 2.6 mt/ha which is not even up to the half of the potential yield of 10 mt/ha. Therefore, this study aimed to measure the involvement level and work performance of extension agents in objective setting, planning, implementing, and monitoring activities in transfer of technology based on Rice Check in IADA Pekan. The study was conducted in Pekan, Pahang and 137 respondents were considered for the 3 schemes which are Pahang Tua, Ganchong and Pulau Jawa. Questionnaire was used to elicit response from the respondents and the data was analyzed using SPSS. Based on the result obtained, the respondents at IADA Pekan has moderate level of practice toward rice check technology and the relationship between management function and work performance is also moderate.